Boys or girls? Sex preferences expressed by women in African and Asian demographic surveys - Michel Garenne; Nancy Stiegler; Jean-Pierre Bouchard (My University, 2023)
In this interview with Jean-Pierre Bouchard, demographers Michel Garenne and Nancy Stiegler explore sex-preferences for girls or boys expressed by women who responded to DHS surveys in twenty-nine African and ten Asian countries. The IPUMS/DHS database was used for statistical analysis, bringing together 140 surveys and 2.5 million women aged 15–49. Overall, two-thirds of women were in favour of a balanced number of girls and boys or were indifferent to the composition of the family. In 20.8% of cases they preferred to have more boys, and in 12.6% of cases they preferred to have more girls. These proportions vary considerably between countries, and were influenced by local culture, religion, level of education, household wealth, and to a smaller extent by urban residence. Sex preferences were also influenced by family composition. These preferences are likely to change rapidly over time. Among the countries analysed, eight expressed preferences for more girls, all located in sub-Saharan Africa, and particularly in southern Africa. These preferences could have many consequences, demographic, social and psychological.